Internal Control System for Cash Receipts in Hospitals - Kalsum, Ummu; Ikhtiari, Kirana (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study aims to evaluate the effectiveness of the internal control system for cash receipts at the Makassar Regional General Hospital, a public healthcare institution under the supervision of the Makassar City government. The research focuses on how well internal controls function to ensure operational smoothness and safeguard cash assets. Research Design and Methodology: A descriptive qualitative approach was adopted to analyze the internal control system in place. Data were collected through interviews and observations as primary sources and supplemented with secondary documentation. The study was conducted at the Makassar Regional General Hospital and focused explicitly on internal processes related to cash receipts. Findings and Discussion: The results indicate that the hospital has implemented a robust internal control system for managing cash receipts, with proper procedures in place, including authorization, documentation, and segregation of duties. Nonetheless, certain areas still show potential for improvement to enhance overall effectiveness and reduce risk exposure. Implications: The findings highlight the importance of robust internal controls in public sector institutions and underscore the need for continuous review. Further research is recommended to compare internal control practices across similar hospitals, contributing to policy development and improved financial accountability in public health services.